Struktur Biaya Usahatani Kentang Berdasar Luas Lahan Garapan - Suminartika, Eti; Djuwendah, Endah (Universitas Galuh, 2025)
Potato farming requires a lot of production costs, most of the farmers in Margamulya village are land tenants and 40% of farmers rely on capital from the city. This condition has an impact on the cultivated land cultivated by farmers. The purpose of this study is to analyze the cost structure of potato farming based on the land area. The research method used is the survey method, the data used consists of primary and secondary data, primary data is obtained from random sample farmers. The analysis used is descriptive analysis and mathematical analysis which includes the proportion of cost components to total costs, revenue analysis and RC ratio. The results of the study show: The production cost of potato farmers in Margamulya village is Rp 81,527,000 per hectare, 93 percent of the total cost is variable costs. The portion of seed costs is the largest (61%), followed by labor costs (21%) and then manure costs (16%) of the total variable costs. The production costs of potato farmers with below-average land area are greater than those of farmers with above-average land area, thus farmers with above-average land area are more efficient in using production costs.